2004
DOI: 10.2172/861308
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Imaging of UXO-Contaminated Underwater Sites (Interim Report)

Abstract: SummaryFinite difference modeling with 2-dimensional models were conducted to evaluate the performance of source-receiver arrays to locate UXO in littoral environments. The model parameters were taken from measurements in coastal areas with typical bay mud and from examples in the literature. Seismic arrays are well suited to focus energy by steering the elements of the array to any point in the medium that acts as an energy source. This principle also applies to seismic waves that are backscattered by buried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Undersea deposition of unexploded ordnance (UXO) from sunken warships, military waste, and navy training is a potential source for contamination of marine environments by explosives such as hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) and octahydro‐1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine (HMX) (Gritto et al , 2004; McDonald et al , 2004; Ek, 2005). Sediments recently collected from UXO‐contaminated sites in Halifax harbor (Darrach et al , 1998) and Hawaii (Monteil‐Rivera et al , 2005) were found to contain traces of explosives.…”
Section: Introductionmentioning
confidence: 99%
“…Undersea deposition of unexploded ordnance (UXO) from sunken warships, military waste, and navy training is a potential source for contamination of marine environments by explosives such as hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) and octahydro‐1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocine (HMX) (Gritto et al , 2004; McDonald et al , 2004; Ek, 2005). Sediments recently collected from UXO‐contaminated sites in Halifax harbor (Darrach et al , 1998) and Hawaii (Monteil‐Rivera et al , 2005) were found to contain traces of explosives.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that traditional seismic survey techniques using geophones have been proposed and recently tried with mixed success for underwater UXO detection. 6 Several past approaches have involved fusion of two or more of these technologies with limited tactical/operational success. 7…”
Section: Existing Detection Methodsmentioning
confidence: 99%